Effect of maturity stages of Fig (Ficus sur) fruits on chemical composition, in vitro digestibility and in sacco dry matter degradability - Diba, D.; Mekasha, Yoseph; Urge, Mengistu; Tolera, Adugna (2014)
The present study was conducted to investigate the effect of fruits maturity stages at harvest on chemical composition, in vitro digestibility and in sacco degradability of Ficus surfruits (FSF). The treatments involved different maturity stages of Ficus sur fruits . Color, moisture content, and texture were used to distinguish among the fruit maturity stages. Fruits at early, mid, and late stages of maturity were collected from five trees and analyzed. The proximate composition of the fruits varied only slightly (0 to 3%) with the progress in maturity of the fruits. The exception was the DM content which increased from 45 to 87% with increasing maturity. The condensed tannins were low (<2%) for all the stages of maturity. In vitro and in sacco measurements indicated that the fruits at all stages of maturity were theoretically only slightly inferior to cereal grains as sources of digestible energy. However, the high washing loss in the in sacco study (38 to 42%) indicates that much of the digestible carbohydrate was in the form of soluble sugars which, depending on the levels used in the diet, could compromise the realizable net energy value of the diet. As in cereal grains, the crude protein content was relatively low (7.07 to 7.33% in DM).